The Influence of Guidance on Construction Bugdet Plan for Local Residents - Alwan Gangsar Brilian Putra; Bambang Sabariman; Erina Rahmadyanti; Mas Suryanto HS HS; Meity Wulandari; Lynda Refnitasari (Jurnal Teknik Sipil, 2024)
The lack of understanding among the community in preparing the Budget Plan (RAB) for construction projects often creates obstacles in project implementation in Kelurahan Ketintang, Surabaya. The Community Service Program (PKM) by Universitas Negeri Surabaya (UNESA) aims to enhance the understanding of the community in RT.03 RW.04 Kelurahan Ketintang in preparing the RAB using Microsoft Excel. This program is conducted in three stages: introduction and socialization, technical guidance, and evaluation. The results indicate an improvement in participants' understanding, with the average score increasing from 42.37 in the pre-test to 63.37 in the post-test, reflecting an average increase of 20.99%. This demonstrates that the program is effective in assisting the community to understand and apply the preparation of the RAB more accurately and efficiently. The program is also expected to support better local infrastructure development and strengthen the relationship between the university and the community.